Visão dos estudantes de administração de uma instituição de ensino superior a respeito do programa Microempreendedor Individual - MEI - Silva, Marcos Manuel da Costa (Brasil, 2024)
Joining the individual micro-entrepreneurship program - IME generates several benefits for a person, such as having a CNPJ, issuing invoices, having social security rights, among others. The general objective of this study is to evaluate the main challenges that prevent informal workers and potential entrepreneurs from formalizing themselves as IME. The methodology adopted consists of descriptive research carried out through a field survey associated with a quantitative approach. A questionnaire with open and closed questions was answered by 20 university students. From the results obtained, it is highlighted that the biggest challenges for entrepreneurs to officially become IME are related to the barriers that exist on the path to formalization, such as: lack of opportunity, fear of having tax problems, lack of knowledge about the program and the fear of starting and then failing. Although the difficulties presented are real, they do not make it impossible to seek legalization to act as a formal entrepreneur.